Sex, politics and empire : A postcolonial geography - Phillips, Richard, 1965- (Book collections on Project MUSE., 2017)
Colonial governments, institutions and companies recognised that in many ways the effective operation of the Empire depended upon sexual arrangements. For example, nuclear families serving agricultural colonization, and prostitutes working for single men who powered armies and plantations, mines and bureaucracies. For this reason they devised elaborate systems of sexual governance, such as attending to marriage and the family. However, they also devoted disproportionate energy to marking and policing the sexual margins. In 'Sex, Politics and Empire', Richard Phillips investigates controversies surrounding prostitution, homosexuality and the age of consent in the British Empire, and revolutionises our notions about the importance of sex as a nexus of imperial power relations.